A Descriptive Study on the Blind Spots of Performance Appraisal in the IT Sector : A Contemporary 360 Degree Approach - Chandhana, K.; Easow, David T. (Prabandhan: Indian Journal of Management, 2018)
Performance appraisal is an important aspect of human resource development mechanism, which is designed specifically for all round development and growth of employees as well as organisations. The term - performance appraisal has recently become a top-notch pick, especially by the IT sector, wherein the top MNCs sacked many employees stating the reason to be poor performance. But is it the real scenario existing in such corporate companies ? This study brought in a contemporary approach to performance appraisal covering the perspectives of employees as well as the appraisers to get a 360 degree view of it. The main purpose of this study was to understand the perceptions of employees and appraisers in the IT sector with regard to performance appraisal. The survey method was used to collect data by using simple random sampling. IT employees (software development life cycle team) and appraisers were the respondents of this study. Companies registered under NASSCOM and STPI in Chennai was the population of the study. The study used multivariate analysis namely factor analysis and paired t - test. It was proved that there existed a difference of opinion between employees and appraisers, which led to mismatch and misconception between them, making the appraisal a failure. Furthermore, this study also identified the key success factors and challenges which would be useful for the industry and academicians to develop a new model or a new appraisal system, which would be beneficial for the employees as well as for the growth in the performance of an organization.